PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO BLOG BERBASIS REELS INSTAGRAM UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA SMPN 2 PASURUAN - Zainullah; Kurniawan, Rudi (Universitas Nahdlatul Ulama Pasuruan, 2023)
This research is to produce learning media that are validso that they are suitable for use in the delivery of learning material. In addition, this study also aims to create learning media that are effective in increasing student interest and motivation. This research is research development (Research and Development). development procedures using the ADDIE model. Using this learning media can increase students' learning interest by 41.3% and increase student learning motivation by 36.5%. As a result of the validation of the material expert and the instructor's evaluation of the Instagram reels-based mathematics learning media video blog, a holistic score of 118 was obtained with a percentage of 87.4% included in the Very Eligible criteria. What will happen is the media expert's validation of the Instagram reels-based mathematics learning media video blog obtained an overall score of 137 with a percentage of 91.3% included in the criteria of Very Eligible and Valid for use in learning activities. So that from material validation andmedia validation it can be concluded that learning media is valid media to use.